Revealing the mismatch in the response to warm-wetting climate of vegetation greenness and primary productivity using MODIS GPP/LAI in Nepal - Dongping Zhong; Lingwen Zeng; Ye Chen; Yingdong Tong; Nana Bai; Jia Sun; Dongdong Zhang; Yingchun Fu (Environmental Research Letters, 2025)
The increasingly warm-wetting climate has gradually promoted vegetation greenness on the Tibetan Plateau and the surrounding region, yet the specific mechanisms driving this change in high-altitude mountainous areas remain unclear. This study, using Nepal as a case study, investigated the spatial and temporal impacts of hydro-climatic factors on leaf area index (LAI) and gross primary productivity (GPP), as well as the coupling degree of GPP-LAI expressed as the correlation coefficient ( R ^2 ) of these trends from 2003 to 2020. The results indicated both GPP and LAI increased significantly more during the dry season than the rainy season in Nepal, but the coupling degree of GPP-LAI in Nepal showed distinct seasonal and elevational differences. Relative to low coupling degree in high and low elevation regions, a higher yet gradually decreasing coupling degree was demonstrated in the mid high regions of central Nepal. By analyzing the effects of elevational profiles, this study revealed that temperature and solar radiation exhibited significant negative correlations with GPP in the southern and central forests at mid elevation, while suggesting a positive correlation in the high mountain alpine forests, which mitigated the limiting effects of precipitation constraints on GPP during the dry season. And the decreased temperature and precipitation had negative impacts on treeline deviation, which led to spatial variations in treeline deviation and coupling degree on either side of the 83°E in the Nepalese Himalayan alpine forests. Additionally, trends of shrubland in GPP and LAI growth reflected adaptations to a warmer and wetter climate. The study about spatio-temporal variation in response to warm-wetting climate, affected by seasons and elevations, offers a scientific basis for the adaptation and conservation of alpine vegetation in Nepal.